New Trends and Applications in Femtosecond Laser Micromachining - Vázquez, Rebeca Martínez; Bragheri, Francesca; Paiè, Petra (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contains the scientific contributions to the Special Issue entitled: "New Trends and Applications in Femtosecond Laser Micromachining". It covers an array of subjects, from the basics of femtosecond laser micromachining to specific applications in a broad spectra of fields such biology, photonics and medicine.